Estudos genéticos e seleção de acessos tradicionais de feijão de corda no Semiárido - Rolim, Rubens Rangel (2022)
Cowpea is an important source of protein for human consumption, in addition is often used in animal feed and organic fertilization. Due to its productive versatility and wide genetic variability, cowpea plant has broad adaptive capacity and low requirements of water and nutrients during management, representing an excellent food alternative especially for populations located at arid and semiarid regions of worldwide. This work aimed to evaluate the genotype x environment interaction and genetic diversity in traditional cowpea varieties, for further selection of parents with broad adaptability and stability, and high agronomic performance for recommendation in breeding works focused on semiarid environment. Additionally, some agronomic traits were discriminated as criteria for use in selection procedures. The assay was carried out in two environments, under rainfed conditions in a Luvisoil, located at “Cariri” region, in Paraiba State, Brazil. Twelve genotypes obtained from local farmers and acquired in street markets were evaluated based on fifteen agronomic traits. The plot consisted of 4 m-four rows spaced of 0.7 m between rows. Plants were spaced in 0.4 m. A randomized blocks was adopted as experimental, with three replications. Data were used to analysis of variance and estimation of genetic parameters. Subsequently, a multivariate analysis was performed with clusters based on the generalized Mahalanobis distance. Simple, canonical and path coefficient were estimated based on means of statistically different traits. Simple interactions were detected for all traits evaluated, indicating that the same genotype may be recommended for both environments studied. Although the performance patterns between the genotypes were similar in both environments, the highest production was found from Fazenda Almas place, due to environmental conservation and greater rainfall. Genetic variability was found among genotypes, as well as superiority of traditional varieties in relation to the controls for yield traits. The more contributive traits for divergence were number of grains per pod, days to maturation, weight of 100 grains and pod length. Based on results obtained via genetic parameters, cluster analysis, morphoagronomic performance and estimated distances, the follows genotypes were identified as the most promising: Cariri, Roxinho, Rabo de Tatu, Corujinha and IPA 207. They are, therefore, recommended for parents in studies of cowpea breeding. The traits number of pods per plant, pod length and weight of 100 grains maximized the correlated response; the adoption of them for composition of selection indices and/or simultaneous selection and traits can contribute to increase the biomass production of genotypes. It is possible to increase the yield and invest in research with cowpea using land race varieties in semiarid environment.